Gerakan Literasi Sains melalui Pengenalan STEAM pada Anak di Komunitas Ã¢â‚¬Å“Panggon MocoÃ¢â‚¬Â Gresik - Sumarno, Wahyu Kyestiati; Shodikin, Ali; Rahmawati, Adinda Aulia; Shafira, Putri Dian; Solikha, ImroÃ¢â‚¬â„¢atus (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
Scientific literacy is one of the important literacies that children need to have. However, there are many findings that show the low level of scientific literacy in Indonesian children.